Wage Policy Impact on Employee Performance in Industry Areas Bekasi District - Sabil Sabil; Mohamad Syamsul Maarif; Edie Toet Hendratno; Widarto Rachbini (DINASTI RESEARCH, 2020)
In the last few years, employee performance has decreased because the wages received are considered insufficient to meet the needs of a decent life. The purpose of this study was to examine and analyze those influencing wage policies and employee performance in companies in the Bekasi Regency industrial area. The study population was employees of companies in the industrial area of ??Bekasi Regency. In accordance with structural equition modeling (SEM), a sample of 285 respondents was selected through a purposive sampling technique. Data analysis was applied by applying government regulation theory, trade union theory, labor productivity theory, wage policy theory and employee performance theory. Hypothesis testing was carried out using SEM with the Lisrel Version 8.80 application. The results showed that the direct effect of government regulations, labor unions, work productivity and living costs has a significant effect on wage policies and government regulations, labor unions, wage policies have a significant effect on employee performance and indirect effects. government regulations, labor unions, work productivity, cost of living, have a significant effect on employee performance through wage policies.